Moral Development of Early Childhood Through Living Values Education - Ria Astuti; Khoirul Bariyyah; Yuli Salis Hijriyani; Thorik Aziz; Elfan Fanhas Fatwa Khomaeny; Nurul Ismaiyah; Yuniatari (Institut Agama Islam Negeri Madura, 2023)
The aim of this study is to describe moral development of early childhood through Living Value Education approach in RA Taiara Chandra Yogyakarta. Basically, this curriculum is character based curriculum. This is qualitative descriptive study by using interview, observation, and documentation. Interview is conducted toward the teacher and headmaser. The result of this study indicates that RA Tiara Chandra using K13 curriculum with Living Value Education approach, which consists of universal value in daily live wether at the school, home or in the society. Based on observation and interview results, many children in this school not on know about some carracter but also know why they should have that carracter. The universal living value that have been integrated in RA Tiara Chandra curriculum namely, peace, honesty, appreciation, responsibility, cooperation, care and share, love, happiness, religious, and freedom. The method tha have been applied are exemplary, habituation, role play, and story telling.